The effect of temperature on low-cycle fatigue of shape memory alloy (Fracture and Structural Integrity, 2019)
The influence of temperature on the fatigue properties of pseudoelastic NiTi under low-cycle fatigue are investigated. Tests were performed under the uniaxial tensile deformation (pull-pull) at 0°С and 20°С which is above the austenite finish temperature. Experimental results indicate that the fatigue life of NiTi alloy increases with the decrease of test temperature from 20°С to 0°С in the case of presenting the results depending on the strain range and Odqvist’s parameter. Regardless the test temperature, with the increase of number of cycles to failure, the stress and strain ranges, as well as the dissipation energy decrease, and the total dissipation energy and Odqvist’s parameter increase. The slope of the fatigue curves of NiTi alloy is greater at the temperature of 0°С in comparison with the 20°С in the case of employing the stress range, strain range, Odqvist’s parameter, and total dissipation energy as the failure criteria, and is less while employing the dissipation energy as the failure criterion.
Keywords: NiTi alloy; Low-cycle fatigue; Odqvist’s parameter; Dissipated energy.; Pseudoelasticity